การดูดซับไนไตรท์และไนเตรทออกจากน้ำเสียสังเคราะห์โดยดินเบาที่ผ่านการเผา - กิติยา น้อยม่วง (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The efficiency of nitrite and nitrate adsorption from synthetic wastewater by calcined diatomite was studied in a batch experiment. The results indicated that the most effective calcined diatomite was a diatomite calcined at 800 ํC. The appropriate condition for nitrite and nitrate adsorption from synthetic wastewater was determined by varying concentration of nitrite and nitrate, pH, contact time and amount of calcined diatomite at room temperature. The results indicated that the efficiency of nitrite adsorption from synthetic wastewater was 96% at 30 mg/l of nitrite concentration using 3 grams of calcined diatomite at pH 2 with shaking rate 200 rpm for 8 hours and the efficiency of nitrate adsorption was 93% at 40 mg/l of nitrate concentration using 3 grams of calcined diatomite at pH 2 with shaking rate 200 rpm for 24 hours. The adsorption isotherm of nitrite and nitrate can be described by the Freundlich isotherm. The study also indicated that the leaching of nitrite and nitrate from calcined diatomite was lower than the level which can harm human beings.